A Method of Conversation Analysis in Narrative and Historical Texts - Leila Nowruzpur; Mahdi Mohammadinejad; nafiseh ghorbanpor (مطالعات زبانی و بلاغی)
Conversational analysis is a field in discourse and researchers in this field have proposed methods for conversation analysis that are not comprehensive for all types of texts. In this article, while introducing these research, we will show how conversation analysis is performed and what questions should be answered. The main problem of this research is to propose a method for analyzing the conversations in literary and narrative texts. Using the existing approaches in linguistics, the method presented is more comprehensive. It seems that in conversation analysis, three levels can be considered: micro level means the structure of language in terms of words, grammatical constructions, sentence construction and metadiscourses. Intermediate level includes sequences and adjacency pairs, turn taking, speech act and implicature, and in macro level, i.e. conversation in relation to social action, frame and genre, and what can be examined at the level of explanation according to Fairclugh view. The approach of this article is theoretical and only one conversation from Beyhaqi’s work has been analyzed. Assuming that this conversation exactly was happened, another valuable aspect of Beyhaqi's history becomes apparent. These conversations reflect the power structure in the different social levels. The analyst, with the help of background knowledge and awareness of the ideas and social expectations accepted by the members of Ghaznavid court society, shows the relationship between discourse actions and social action.